A scoping review on the conduct and reporting of scoping reviews - Tricco, Andrea C.; Lillie, Erin; Zarin, Wasifa; O’Brien, Kelly; Colquhoun, Heather; Kastner, Monika; Levac, Danielle; Ng, Carmen; Sharpe, Jane Pearson; Wilson, Katherine; Kenny, Meghan; Warren, Rachel; et al. (BMC medical research methodology, 2016)
Background Scoping reviews are used to identify knowledge gaps, set research agendas, and identify implications for decision-making. The conduct and reporting of scoping reviews is inconsistent in the literature. We conducted a scoping review to identify: papers that utilized and/or described scoping review methods; guidelines for reporting scoping reviews; and studies that assessed the quality of reporting of scoping reviews. Methods We searched nine electronic databases for published and unpublished literature scoping review papers, scoping review methodology, and reporting guidance for scoping reviews. Two independent reviewers screened citations for inclusion. Data abstraction was performed by one reviewer and verified by a second reviewer. Quantitative (e.g. frequencies of methods) and qualitative (i.e. content analysis of the methods) syntheses were conducted. Results After searching 1525 citations and 874 full-text papers, 516 articles were included, of which 494 were scoping reviews. The 494 scoping reviews were disseminated between 1999 and 2014, with 45 % published after 2012. Most of the scoping reviews were conducted in North America (53 %) or Europe (38 %), and reported a public source of funding (64 %). The number of studies included in the scoping reviews ranged from 1 to 2600 (mean of 118). Using the Joanna Briggs Institute methodology guidance for scoping reviews, only 13 % of the scoping reviews reported the use of a protocol, 36 % used two reviewers for selecting citations for inclusion, 29 % used two reviewers for full-text screening, 30 % used two reviewers for data charting, and 43 % used a pre-defined charting form. In most cases, the results of the scoping review were used to identify evidence gaps (85 %), provide recommendations for future research (84 %), or identify strengths and limitations (69 %). We did not identify any guidelines for reporting scoping reviews or studies that assessed the quality of scoping review reporting. Conclusion The number of scoping reviews conducted per year has steadily increased since 2012. Scoping reviews are used to inform research agendas and identify implications for policy or practice. As such, improvements in reporting and conduct are imperative. Further research on scoping review methodology is warranted, and in particular, there is need for a guideline to standardize reporting.